Microbiota instruct IL-17A-producing innate lymphoid cells to promote skin inflammation in cutaneous leishmaniasis. - Tej Pratap Singh (Public Library of Science (PLoS), 2021)
Innate lymphoid cells (ILCs) comprise a heterogeneous population of immune cells that maintain barrier function and can initiate a protective or pathological immune response upon infection. Here we show the involvement of IL-17A-producing ILCs in microbiota-driven immunopathology in cutaneous leishmaniasis. IL-17A-producing ILCs were RORγt+ and were enriched in Leishmania major infected skin, and topical colonization with Staphylococcus epidermidis before L. major infection exacerbated the skin inflammatory responses and IL-17A-producing RORγt+ ILC accumulation without impacting type 1 immune responses. IL-17A responses in ILCs were directed by Batf3 dependent CD103+ dendritic cells and IL-23. Moreover, experiments using Rag1-/- mice established that IL-17A+ ILCs were sufficient in driving the inflammatory responses as depletion of ILCs or neutralization of IL-17A diminished the microbiota mediated immunopathology. Taken together, this study indicates that the skin microbiota promotes RORγt+ IL-17A-producing ILCs, which augment the skin inflammation in cutaneous leishmaniasis.